2003
DOI: 10.1128/mcb.23.5.1808-1816.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of Distinct Histone Modifications during Collagenase Gene Activation

Abstract: Gene activation in eukaryotes requires chromatin remodeling, in part via histone modifications. To study the events at the promoter of a mitogen-inducible gene, we examined the induction of expression of the collagenase gene. It has been established that the collagenase gene can be activated by c-Jun and c-Fos and that the transcriptional coactivator p300 is involved in the activation. As expected, we found histone acetyltransferase activity at the collagenase promoter during activation. Interestingly, we also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 55 publications
4
72
0
1
Order By: Relevance
“…We find that the Gcn5 histone acetyltransferase activity is required for SWI/SNF to stably associate with the HO promoter, at least in the presence of the Ash1 negative regulator. Sequential recruitment of transcription factors has also been seen at other genes, including the human beta interferon, ␣1 antitrypsin, collagenase, and PPAR␥2 genes (2,58,73,77), and for each of these promoters, binding of a Gcn5-like histone acetyltransferase precedes SWI/SNF binding (2,58,73,77). It has also been shown that histone acetylation precedes SWI/SNF bind- ing at the myogenin promoter (29) and that a gcn5 mutation reduces the rate at which SWI/SNF is recruited to the SUC2 promoter following induction (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that the Gcn5 histone acetyltransferase activity is required for SWI/SNF to stably associate with the HO promoter, at least in the presence of the Ash1 negative regulator. Sequential recruitment of transcription factors has also been seen at other genes, including the human beta interferon, ␣1 antitrypsin, collagenase, and PPAR␥2 genes (2,58,73,77), and for each of these promoters, binding of a Gcn5-like histone acetyltransferase precedes SWI/SNF binding (2,58,73,77). It has also been shown that histone acetylation precedes SWI/SNF bind- ing at the myogenin promoter (29) and that a gcn5 mutation reduces the rate at which SWI/SNF is recruited to the SUC2 promoter following induction (35).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, Mediator binds to the TATA region, dependent on the SBF factor. Activation of the Cdc28 cyclin-dependent kinase is required for binding of RNA polymerase, TFIIB, and TFIIH at the HO TATA (24).Ordered recruitment of transcription factors has also been seen at other promoters (for a review, see reference 23), including the human beta interferon, ␣1 antitrypsin, collagenase, and PPAR␥2 promoters (2,58,73,77). For example, at the beta interferon promoter, binding of sequence-specific factors results in the sequential recruitment of the Gcn5 complex, followed by the CBP-RNA Pol II complex and then the SWI/SNF complex (2).…”
mentioning
confidence: 99%
“…Similarly, at the inducible collagenase promoter, which has been shown to be rapidly dimethylated at H3-K4 following mitogen stimulation (48), preincubation with 2 mM MTA blocked the induction of the gene. Our results are in accordance with these data and argue for a positive role of H3-K4 dimethylation in regulating transcription of adipogenic genes and ultimately, the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…PCAF can associate with CBP and with nuclear receptors independently of CBP (5). p300/CBP has been shown to activate the collagenase type I gene via AP-1 sites (24). CBP also was required for the activation of RA responsive genes, and inhibition of AP-1 activity by RA was attributed to RAR competition for limiting amounts of CBP.…”
mentioning
confidence: 99%